Implementasi Peraturan Keselamatan dan Kesehatan Kerja (K3) pada Proyek Pembangunan Perumahan di Wilayah DIY - Elza Qorina Pangestika (Jurnal Hukum Sasana, 2023)
Housing construction projects do not only depend on time management, costs, good quality, but their implementation also needs to pay attention to occupational safety and health (K3) in the project environment. Housing construction is an activity that uses quite a lot of equipment, both sophisticated and manual. The equipment is used in large areas with various types of activities causing a high risk of accidents. Basically the housing construction process is an activity that contains many elements of danger. The problem of work accidents affecting housing construction workers is quite an interesting issue, considering that boards are one of the primary human needs, and housing construction activities are very close to our lives.